Editorial Vol.1 (Siddhajyoti Interdisciplinary Journal, 2020)
Siddajyoti Education Campus (SJEC) is a community campus located at Kamalamai Municipality-5, Phosretar, a rural area of Sindhuli district. The campus is affiliated with  Tribhuvan University, and managed by the local community envisioning to stand as one of the leading academic institutions in the country for quality education and promoting research activities. It follows the rules, regulations, guidelines, curriculum, examination system, and other academic norms of Tribhuvan University. The campus enrolls and provides support to the students of rural areas in this region particularly Chhori (daughters) and Buhari (daughters-in-law).Since research is to create new knowledge and to use the existing bodies of knowledge in a new and creative ways so as to generate new concepts, methodologies and understandings, SJEC believes on developing research culture for effective, meaningful and productive classroom instruction in this ever-changing world. Apprehending this reality SJEC has established Research Management Cell (RMC) with the support of University Grants Commission (UGC). RMC has been launching research oriented trainings, workshops, seminars, course refresher trainings, capacity development trainings to develop professional skills of teachers as well as students. RMC also supports teachers for doing mini researches, and students for thesis writing.SJEC believes that delivering lecture and providing the same old notes culture has been failure in our context. Therefore, RMC decided to publish research-based academic journal, Siddhajyoti Interdisciplinary Journal (SIJ), an official journal of SJEC. It aims to encourage teachers to read, write and share their researches and ideas among teachers, trainers, researchers, policy makers, and practitioners of interdisciplinary subjects (Education, Curriculum, Psychology, EPM, English, Nepali, Mathematics, Social, Population, Economics, Health and physical Education etc.) in the academic world through publication.In this first volume of Siddhajyoti Interdisciplinary Journal (SIJ), we have included 15 articles by following rigorous peer review and editing process. This volume includes the articles of novice scholars of Nepal from English, Health, Economics, Nepali, Education and Mathematics backgrounds. In the article from Nepali discipline Dr. Jibalal Basyal explores the contemporary issues of writing Nepali poem, Surendra Bam, Heramba Raj Bastola, Ramesh Bhattrai, Krishna Prasad Subedi and Jhagindra Raj Dhakal analyse and synthesise the ideas of professional development of language teacher, role of teaching materials in multilingual class, self evaluation practice in instruction development, different aspects of origin of language and various types and ways of reading, respectively. In English Nani Babu Ghimire explores the responsibilities and expectation of the teachers of community campus for their professional development, Man Bahadur Jora talks about the burning issue of English Medium Instruction regarding ethnics groups' parents believe on it, Dipak Tamang attempted to justify the language policy in Nepal concerning on multilingual practice in family, and Sakun Kumar Joshi discusses about linguistic intelligences at basic level learners in Nepal. Likewise, Keshar Bahadur Kunwar argues on foreign direct investment and economic growth of Nepal, Yam Prasad  Pandeya looks into parental factors and their effects on students' learning in mathematics, Sapana Adhikari investigates struggle of Tamang children in achieving elementary education, Shanti Devi Rai explains Suptulung as indigenous knowledge of Kirat Rai people in Nepal. Exploring the issue of Health education Kosh Bilash Bagale avers about menstruation as still dark side of the society in 21th century in Nepal.We are very confident that these articles will be instrumental in guiding the coming generations of multidisciplinary practitioners of Nepal. We make call to all valuable readers to contribute by writing for the upcoming issues, reading articles and writing comments as well as bringing changes in your profession. Let's try our hand not only in the classroom but also in strengthening our academic development through this publication.We express our gratitude to all authors for their valuable contributions. Our sincere gratitude goes to all reviewers, who supported the Editorial Team throughout the process. We are equally grateful to Campus Management Committee of SJEC and RMC for their continuous support. We are also thankful to the designer, Prakhar Sindhuliya for the elegant design.Happy reading!